Genetic Relationship Between Heavy Metals Resistance and Î²- Lactamase Production In E. Coli and Staphylococcus Aureus - Husein, A.S . (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
This study is a trail to know if the genes controlling some of heavy metals resistance ( lead, zinc, cadmium, cromium) in two types of pathogenic bacteria E. coli as gram negative bacteria and S. aureus as gram positive bacteria, present on the Î²-lactamase plasmid. Ten isolates of each bacterial types which produced Î²-lactamase enzyme, were cultivated in the presence of acridine orange. The growing in the presence of acridine orange resulted in loss of the Î²-lactamase genes in S. aureus and E. coli, and loss of the heavy metals resistance in S. aureus, while the resistance of E. coli against heavy metals still without any change. The results indicate that the genes for heavy metals resistance exist on the Î²-lactamase plasmid in S. aureus only, while in E. coli the genes that controlling heavy metals resistance are not on Î²lactamase plasmid